Prevalence, socio-demographic characteristic and associated medical factors of teenage pregnancy in selected maternal and child health clinics in Kuching - Soe, Min Htut (Universiti Malaysia Sarawak (UNIMAS), 2010)
Teenage pregnancy is an important public health problem as it often occurs in the context of poor social support and maternal wellbeing. A retrospective cross sectional study was done among registered teenagers who attended antenatal follow-up at three maternal & child health clinics (MCHC) in Kuching namely, MCHC Jawa, MCHC Sekama, and MCHC at Polyclinic Tanah Puteh. The aim of this study is to detennine the prevalence of teenage pregnancy in the community, its socio-demographic characteristics, and associated medical and health facto~There was a total of 334 teenage "mothers attending to the selected three MCHCs with the prevalence rate of 5.29 percent. Majority of the teenage mothers were of MalaylMelanau ethnicity (42.8%), 75.1 % were married, 74.2% achieved at least secondary education level, 58.1 % were housewives and 79.6% were in their first pregnancy. Good antenatal follow-up was seen among 43.3% of married teenage mothers, 55.0% of late teen, 59.4 % of housewives and also 78.4% of those'having their antenatal booking done in the first trimester. The first antenatal registration to the clinic done in the third trimester was more common among unmarried teenage mothers (43.4%). Anaemia was the most common complication (46.1 %) and more commonly seen in teens (59.4%) than late teens (48.1 %). Majority (85.5%) of teenage mothers had spontaneous vaginal delivery. Among those who have delivered, 11 % of the neonates had low birth weight while 18.1 % of them were pretenn. The poor postnatal follow-up was more commonly seen in teens (63.0%) than late teens (48.9%). Though the teenage mothers have increased risks of adverse pregnancy outcomes, the problems can be overcome by means of complete coverage of high quality maternity care usually provided in maternal and child health clinics.